2019
DOI: 10.1063/1.5095884
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetic droplet microfluidics applied to single-cell sorting

Abstract: The heterogeneity of diseased tissue causes major challenges in the detection and treatment of disease. Such challenges have motivated the development of tools for single-cell isolation and analysis. However, many cell isolation methods in microfluidics rely on the use of cell-labeling steps or expose cells to potentially harmful forces. Here, we present a microfluidic method for label-free control of cell-encapsulating biocompatible droplets using negative magnetophoresis. Our system is distinguished from pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Buryk-Iggers et al 123 demonstrated a diamagnetic droplet microfluidic method in which cell-encapsulating droplets were precisely controlled based on magnetophoresis, a phenomenon where particles migrate in a magnetic field. The droplet phase was comprised of cells suspended in culture medium, and the magnetic content was contained in the continuous phase.…”
Section: ■ Cell Separation Methodsmentioning
confidence: 99%
“…Buryk-Iggers et al 123 demonstrated a diamagnetic droplet microfluidic method in which cell-encapsulating droplets were precisely controlled based on magnetophoresis, a phenomenon where particles migrate in a magnetic field. The droplet phase was comprised of cells suspended in culture medium, and the magnetic content was contained in the continuous phase.…”
Section: ■ Cell Separation Methodsmentioning
confidence: 99%
“…The application of a magnetic field on droplets rendered diamagnetic by the addition of ferromagnetic fluids (e.g., loaded with paramagnetic beads) can be used to place them into specific areas on chips . As an example, this method has been applied to separate empty droplets from cell-containing drops. , Other protocols have used acoustophoresis for droplet sorting, where piezoelectric transducers produce acoustic waves that can generate a pressure capable to modify the direction of the droplet movement in a flow . This method was applied for isolating cancer cells (HeLa) or for separating live and fixed cells from a mixed population (MCF-7). , …”
Section: Characterizing Cell Behaviormentioning
confidence: 99%
“…Microfluidics is able to control fluid flow precisely in the microchannel that usually presents in multiphase flow [1]. This technology has been successfully implemented in several fields as follows: lab on a chip [2], drug delivery [3], bio-medical [4], digital polymerase chain reaction (ddPCR) procedure [5], cell sorting [6], food industry [7] and chemical [8]. Although microfluidics plays an essential role in many sectors, the current development of this technology focuses on drug delivery since the world has been impinged by the Covid-19 pandemic for the last two years.…”
Section: Introductionmentioning
confidence: 99%